Emergent Typologies of Small Businesses in a Multi-ethnic Wet Market in Malaysia: A Phenomenological Study - Teik Aun Wong (Journal of Business and Social Review in Emerging Economies, 2019)
Small businesses are an invaluable source of local knowledge that provide insights into indigenous commercial, cultural and social values and beliefs.  This article explores various emergent typologies of small businesses in a multi-ethnic Southeast Asian wet market principally with regards to their social responsibility and sustainability.  The field site is Jelutong wet market in Penang, Malaysia.  The philosophical and methodological framework is phenomenology, and principal data-collection tool is semi-structured interview.  Thirty (30) primary interviews and five (5) verification interviews were conducted in various local languages and dialects.  Three (3) typologies emerged and named the Lifestyle, Livelihood and Legacy typologies.    Identifying and understanding these three (3) typologies in small businesses provide important inputs for public policy.